5-Hydroxytryptophan Suppresses the Abdominal Fat Deposit and Is Beneficial to the Intestinal Immune Function in Broilers - Wang, Hui; Liu, Shaoqiong; Li, Jun; Wang, Liyuan; Wang, Xiaojuan; Zhao, Jingpeng; Jiao, Hongchao; Lin, Hai (Frontiers in Physiology, 2020)
ABSTRACT Background: Serotonin (5-HT), a monoaminergic neurotransmitter, involves in the regulation of many physiological functions. In the present study, the effects of 5-hydroxytryptophan (5-HTP), the precursor of 5-HT, on lipid metabolism and intestinal immune function in broiler chickens were investigated in chickens. Methods: Two hundred broilers were divided randomly into two groups and fed separately with a corn-soybean basal diet (CD) or the basal diet supplemented with 0.2% 5-HTP. Results: The results showed that 5-HTP reduced (P<0.05) feed intake and the abdominal fat pad weight. 5-HTP treatment tended to upregulate the mRNA level of adiponectin receptor 1 (ADP1R) and ADP2R in abdominal fat but had no significant influence on their protein levels (P>0.05). In 5-HTP-chickens, lipopolysaccharide exposure decreased secretory immunoglobulin A (sIgA) concentrations in serum and the duodenal contents. Expression of mRNA encoding interleukin (IL), tumor necrosis factor-α (TNF-α), and transforming growth factor-β (TGF-β) decreased after 5-HTP treatment; however, LPS increased expression significantly in 5-HTP-treated chickens compared with CD chickens. In 5-HTP-chickens, the phosphorylation of mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB) were reduced, but the phosphorylation of ribosomal p70S6 kinase (p70S6K) was increased in the duodenum. Conclusion: In summary, the result suggests that dietary 5-HTP supplementation reduces accumulation of abdominal fat and is beneficial to intestinal immune function.